Strategies for the refurbishment of a typical UK end-terraced 100 years old house - Barbhuiya, S.; Barbhuiya, Salim; Nikraz, Hamid (Global Science & Technology Forum, 2013)
In this paper various alternative strategies for the refurbishment of an end-terraced house built in 1909 located in Loughborough, UK have been discussed. The existing house has a SAP rating of 41 and an EPC rating band E. The total CO2 emission of the house is 7.737 tonnes per year. The house spends £1436.66 pa out of a total income of £11,377.00, which means that 12.6% of its income is spent on fuel bill, and can be considered to be in fuel poverty. In order to select the most cost and energy efficient refurbishment measures to be implemented in the house various measures were considered one by one using SAP. The installation costs, reduction in energy demand, energy cost and CO2 emissions and the simple payback time of each measure were studied. Based on this, three options have been considered whereby various measures are combined to analyse the overall impact on the energy efficiency of the house. Option 2 is recommended as the best refurbishment option. The measures which were considered in this option include external wall insulation, loft insulation top-up, door insulation, insulation of primary pipework and hot water cylinder, low energy lighting, replacement of boiler with heating controls, draught proofing and double glazing. This will lead to an increase in SAP rating of 74 which will lift the house to EPC band C. It will also move the household out of fuel poverty.